The Influence of the Snowball Throwing Learning Model on Social Studies Learning Outcomes for Class VIII Students of UPTD SMP NEGERI 1 PEMATANG SIANTAR - Jeli Lusiana D.T. Padang; Binsar Tison Gultom; Pdt. Paulina HN Sirait (MultiTech Publisher, 2023)
This research aims to determine the influence of the Snowball Throwing Learning Model on the Social Sciences Learning Outcomes of Class VIII UPTD Students at SMP Negeri 1 Pematang Siantar. This type of research is quasi-experimental research with a quantitative approach. The population of this study was all class VIII students at UPTD SMP Negeri 1 Pematang Siantar, totaling 347 students. The sample in this study consisted of two classes, namely: Class VIII 4 as a control class with a total of 32 students and Class VIII 7 as an experimental class with a total of 32 students. In this research the instrument used was the test. The data collection technique uses tests, observation and documentation. Meanwhile, the data analysis techniques used are normality test, homogeneity test and t hypothesis testing ( Independent Samples Test ) using the SPSS version 23 application. ​Based on the results of data analysis using t hypothesis testing ( Independent Samples Test ), it was obtained that t = 2,504 and t table (at the 5% significance level) = 1,999, meaning t count > t table . In accordance with the criteria, H 0 is accepted if t count <t table and H 0 is rejected if t count > t table . So, it can be concluded that there is an influence of the Snowball Throwing Learning Model on the Social Sciences Learning Outcomes of Class VIII UPTD Students at SMP Negeri 1 Pematang Siantar.